Blockchain Teaching Simulation Using Gamification - Latifah, Haznah; Fauziah, Zaleha (Pandawan, 2022)
A public blockchain simulation, which bears some resemblance to Bitcoin. All players are interconnected with several possibilities to form coin and block transactions and the power to get a taste of the consensus algorithm controlling transactions and blocks. A software medium that is based on blockchain games began using whiteboards to become web-based simulation games with various teaching scenarios. Contributive tool-based instruction with experience in blockchain concepts that can be used in the classroom as well as online. Along with this, simulations can give students the opportunity to experiment with all relevant blockchain operations like signing, creating transactions, building blocks, etc. This post was written to offer our firsthand experience teaching evolving blockchain technology to business and business information technology students at the undergraduate and graduate levels using newly built gamification teaching applications. This research is based on a design-based research methodology. We describe the process from identifying the problem, to designing the tool and demonstrating its implementation.